2015
DOI: 10.2174/1570159x13666150216222543
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 Channel: A Potential Drug Target for Treating Epilepsy

Abstract: Epilepsy has 2-3% incidence worldwide. However, present antiepileptic drugs provide only partial control of seizures. Calcium ion accumulation in hippocampal neurons has long been known as a major contributor to the etiology of epilepsy. TRPV1 is a calcium-permeable channel and mediator of epilepsy in the hippocampus. TRPV1 is expressed in epileptic brain areas such as CA1 area and dentate gyrus of the hippocampus. Here the author reviews the patent literature on novel molecules targeting TRPV1 that are curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 79 publications
2
61
0
Order By: Relevance
“…Accumulating evidences indicated that activations of TRPM2 and TRPV1 channels are increased in brain injury-induced mitochondrial activation and excessive Free oxygen radical production by the excessive mitochondrial Ca 2+ uptake6929. Furthermore, DEX induces antioxidant effects in the spinal cord (DRG) injuries and cerebral ischemia (hippocampus) of rats11819.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidences indicated that activations of TRPM2 and TRPV1 channels are increased in brain injury-induced mitochondrial activation and excessive Free oxygen radical production by the excessive mitochondrial Ca 2+ uptake6929. Furthermore, DEX induces antioxidant effects in the spinal cord (DRG) injuries and cerebral ischemia (hippocampus) of rats11819.…”
Section: Discussionmentioning
confidence: 99%
“…Transient receptor potential (TRP) family is containing 8 subfamily. Melastatin and vanilloid subfamilies include TRP melastatin 2 (TRPM2) and TRP vanilloid 1 (TRPV1) Ca 2+ permeable cation channels49. Capsaicin (CAP) is a pungent component of hot chili peppers, and TRPV1 is activated by different stimuli, including CAP 10 and oxidative stress11.…”
mentioning
confidence: 99%
“…Blockade of TRPV1 channels by capsazepine administration remarkably suppressed in vivo ongoing ictal activity . Recently, Nazıroğlu presents a revision that support a role for Ca 2+ accumulation through TRPV1 channels in the aetiology of epileptic seizures, indicating that inhibition of TRPV1 in the hippocampus may possibly be a novel target for prevention of epileptic seizures …”
Section: Resultsmentioning
confidence: 99%
“…A growing number of recent studies indicate the involvement of TRPV1 receptors in the etiopathogenesis of epilepsy . Very recently, functional TRPV1 channels have been found in the hippocampus, an epileptic area of the brain.…”
Section: Pathophysiological Rolesmentioning
confidence: 99%